IMPACT OF CURRENT RATIO, PROFITABILITY, CAPITAL STRUCTURE AND COMPANY SIZE ON DIVIDEND POLICY IN IDX - Steven W; Robin Robin; Nico Nico; Rafida Khairani (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
Companies listed on the IDX comprise of various industries, but the one most dominated by investors is consumer goods, since the products being exchanged are constantly required. The aim of this research was to investigate the impact of current ratio, profitability, capital structure and business size on dividend policy in consumer products firms listed on the 2015-2019 Indonesia Stock Exchange. Approaching quantitative research. This quantitative descriptive research kind. This research's nature is cause and effect. This study's population was 51 Consumer Goods Companies listed on the 2015-2019 Indonesia Stock Exchange. The sample is 17 firms. As a consequence, the current ratio has no impact on the dividend policy in Consumer Goods Companies listed on the 2015-2019 Indonesia Stock Exchange. Profitability affects the dividend policy of Consumer Goods Companies listed on the 2015-2019 Indonesia Stock Exchange. Capital structure has no impact on the 2015-2019 dividend policy of Consumer Goods Companies listed on the Indonesia Stock Exchange. Company size has no impact on dividend policy in Consumer Goods Companies listed on the 2015-2019 Indonesia Stock Exchange. Current ratio, profitability, capital structure and size influence the dividend policy of Consumer Goods Companies listed on the Indonesian stock exchange for 2015-2019